-0.2(x+3)=0.3(x+11)

Simple and best practice solution for -0.2(x+3)=0.3(x+11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -0.2(x+3)=0.3(x+11) equation:


Simplifying
-0.2(x + 3) = 0.3(x + 11)

Reorder the terms:
-0.2(3 + x) = 0.3(x + 11)
(3 * -0.2 + x * -0.2) = 0.3(x + 11)
(-0.6 + -0.2x) = 0.3(x + 11)

Reorder the terms:
-0.6 + -0.2x = 0.3(11 + x)
-0.6 + -0.2x = (11 * 0.3 + x * 0.3)
-0.6 + -0.2x = (3.3 + 0.3x)

Solving
-0.6 + -0.2x = 3.3 + 0.3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.3x' to each side of the equation.
-0.6 + -0.2x + -0.3x = 3.3 + 0.3x + -0.3x

Combine like terms: -0.2x + -0.3x = -0.5x
-0.6 + -0.5x = 3.3 + 0.3x + -0.3x

Combine like terms: 0.3x + -0.3x = 0.0
-0.6 + -0.5x = 3.3 + 0.0
-0.6 + -0.5x = 3.3

Add '0.6' to each side of the equation.
-0.6 + 0.6 + -0.5x = 3.3 + 0.6

Combine like terms: -0.6 + 0.6 = 0.0
0.0 + -0.5x = 3.3 + 0.6
-0.5x = 3.3 + 0.6

Combine like terms: 3.3 + 0.6 = 3.9
-0.5x = 3.9

Divide each side by '-0.5'.
x = -7.8

Simplifying
x = -7.8

See similar equations:

| 9x(x)+47x+44=0 | | 2x(x)+x-2x-1=3x+6+9x | | 5x^2-60x+15=0 | | 3x^2+9x-36=0 | | a^2b-25b= | | 8x+0=72 | | 2(w+5)-8w=28 | | x^4+3x^3-28x=0 | | x^3+3x^2-28=0 | | 9(4x-6)=3(12x+8) | | 3+2x-1=9z+6-6z | | 4y+12y=128 | | 7-4+(3*0)+1= | | 7-4(3*0)+1= | | 84x=7x | | -7(4b+2)+(29b-5)=0 | | -416.72x^2+4416.7x+8500= | | 2(5x+1)=12x-2 | | log(2*x+50)=2 | | 7(t-3)+5t=4(3t+3)-8 | | 3(2x+6)=16+2 | | -(5y+5)-(-y-6)=0 | | 2m-3(3m-7)= | | 11x-173=5x-11 | | 4m-7m-3n+3m= | | 4x-8x+5y-10y= | | 4z^2-24z-73=0 | | 7-8x=34-15x | | -(3y+1)-(-2y-6)=2 | | 4*4+4*4+4-4*4=0 | | x-8.2=-4.2 | | -r^2+6r-5=0 |

Equations solver categories